Effect of a Malay Language Phonics Intervention on the Decoding Skills and Self-Regulated Learning Strategies of Older Primary School Students with Dyslexia - Ann Sien Sut Lee; Lay Wah Lee (Kajian Malaysia, 2026)
A Malay language dyslexia intervention programme named “MyBaca” has been developed based on the Orton-Gillingham approach to teach Malay phonics knowledge and decoding skills to children with dyslexia. The present study investigated the effect of the phonics intervention in MyBaca on the decoding skills and self-regulated learning (SRL) strategies of older children with dyslexia. Three children aged 11 years with a dyslexia profile were sampled and taught the MyBaca phonics intervention in 36 individual sessions. An adapted single-subject research design was applied to gather decoding skills scores across baseline, treatment and maintenance phases. A participant observation method was used to gather qualitative narration on SRL strategies. The quantitative results indicate improvement in decoding skills after intervention, more significantly for phonics knowledge involving digraphs. The findings support that teaching of graphemephoneme knowledge, integrated with phonological manipulation skills within an explicit and systematic context is crucial for older children with dyslexia to acquire decoding skills. The qualitative results reveal the development of SRL facilitated by the tutor. In conclusion, the findings are significant as the broader implication is that the traditional syllable-spell method of teaching word reading is insufficient for children with dyslexia and they require more structured instruction in Malay phonics as in the MyBaca programme. The Malay language teachers as well as the remedial and special education teachers need to be aware of these findings in order to ameliorate reading among children with dyslexia.